(untitled) (The Journal of Plant Protection Sciences, 2020)
Like any other branch of Agricultural Sciences, the Division of Nematology at IARI, initiated researches in the exciting field of biochemistry and molecular biology of plant parasitic nematodes during the early seventies of last century. The main research areas were biochemical mechanism of resistance against phytonematodes and diagnostics of economically important plant parasitic nematodes.